2011
DOI: 10.1186/1475-9276-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of need and access to health care in rural population: an ecological study in Iran

Abstract: IntroductionEquity in access to and utilization of health services is a common goal of policy-makers in most countries. The current study aimed to evaluate the distribution of need and access to health care services among Iran's rural population between 2006 and 2009.MethodsCensus data on population's characteristics in each province were obtained from the Statistical Centre of Iran and National Organization for civil registration. Data about the Rural Health Houses (RHHs) were obtained from the Ministry of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…We used the Gini coefficient and the index of dissimilarity which are both commonly used in analysing inequality in the distribution of health care resources (10,22,23).…”
Section: Inequality Measures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Gini coefficient and the index of dissimilarity which are both commonly used in analysing inequality in the distribution of health care resources (10,22,23).…”
Section: Inequality Measures and Data Analysismentioning
confidence: 99%
“…While there is a positive relationship between the geographical availability of health care resources and the health status of populations, increasing health care resources alone does not necessarily lead to improved health outcomes. People regardless of their race, sex and geographical region should be guaranteed fair access to health care services (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The former was obtained by dividing the coverage range into ten equal parts and representing each decile of coverage along the horizontal axis with the percentage of the total available to the population on the ordinate axis. The Gini index was estimated according to the methods proposed by for grouped data, with zero corresponding to perfect equality (everyone has access to the same resources) and 1 corresponding to perfect inequality (only one person has all the resources and the others have nothing) [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…In another study, in evaluating the geographical distribution of ICU beds for non-cardiac diseases in Iran, showed that the distribution of intensive care unit beds in the provinces of the counCopyright © 2018, Shiraz E-Medical Journal. This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited U n C o r r e c t e d P r o o f try was fair, however, the number of beds was lower than in other countries (14). In addition, In another study, in regards to examining the geographical distribution of access to health care in rural areas, have shown that there is a significant difference in the distribution of health house based on rural mortality rates (15).…”
Section: Introductionmentioning
confidence: 99%